Inhibition of agrin-induced acetylcholine-receptor aggregation by heparin, heparan sulfate, and other polyanions - Wallace, BG (J Neurosci, 1990)
Heparin and heparan sulfate have been shown to block nerve-induced acetylcholine-receptor (AChR) aggregation at developing neuromuscular junctions. We found that heparin, heparan sulfate, and a wide variety of other polyanions also inhibited agrin-induced AChR aggregation. The more highly charged the polyanion, the more potent it was as an inhibitor. Inhibition of agrin-induced AChR aggregation was due, at least in part, to the formation of a complex between the polyanion and agrin that was inactive. These findings are consistent with the hypothesis that nerve-induced aggregation of AChRs is mediated by the release of agrin, or a closely related protein, from axon terminals and suggest that a polyanion, such as a sulfated proteoglycan, may be involved in the interaction of agrin with its receptor on the myotube surface.